UPAYA MENINGKATKAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN BAHASA ARAB MATERI A`ḌĀ’U AL-JISMI MELALUI METODE TEAMS GAMES TOURNAMENT (TGT) SISWA KELAS I-B SMP SWASTA GALIH AGUNG - Nurainun Hasibuan; Rahmadani Fitri Ginting; Rahmiatul Fitri (Yayasan Haiah Nusratul Islam, Indonesia, 2026)
This research aims to improve student learning motivation in Arabic subjects on A`ḍā’u al-jismi material through the Teams Games Tournament (TGT) method for Class I-Bstudents at Galih Agung Private Junior High School. This research uses the Kemmis & McTaggart classroom action research model. The research consists of 2 cycles with four components or actions, namely: planning, implementation, observation, and reflection in each cycle. The data collection methods used in this research include: (1) Observation, (2) Tests, (3) Documentation. The data collected from these three methods is then analyzed to obtain research results. The conclusion of the research results shows that; (1) Student learning motivation in Arabic subjects on A`ḍā’u al-jismi material for Class I-Bstudents at Galih Agung Private Junior High School was still low in the initial observation, the researcher found a lack of participation and enthusiasm of students in learning activities which affected the low learning outcomes of students, (2) The application of the Teams Games Tournament (TGT) method in Arabic subjects on A`ḍā’u al-jismi material is by holding games and tournaments in the learning process, (3) The increase in learning motivation of Class I-Bstudents at Galih Agung Private Junior High School in Arabic subjects on A`ḍā’u al-jismi material is marked by increased participation and activeness of students in learning and student learning outcomes. In the pre-cycle, low participation and enthusiasm of students in learning activities were seen, and the classical completeness obtained by students was 22.7%. In Cycle I, the assessment of student activity obtained an average score of 2.24, and the classical completeness obtained by students was 65%. While in Cycle II, the assessment of student activity increased with an average score of 3.52, and the classical completeness obtained by students was 90%.